2022
DOI: 10.1002/2211-5463.13390
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection affects the human gastric microbiome, as revealed by metagenomic sequencing

Abstract: Helicobacter pylori infection is a prevalent infectious disease, associated with many gastric diseases, including gastritis, gastric ulcer, and gastric cancer. To reveal the characteristics of the gastric microbiome in patients infected with H. pylori, we performed metagenomic shotgun sequencing of stomach swab samples from 96 patients and then conducted metagenomic association analyses between alterations in the gastric microbiome and H. pylori infection status. The overall composition of the gastric microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…39 A number of authors grouped Helicobacter into Proteobacteria in their articles. 14,16 While the Epsilonproteobacteria constitute a stable monophyletic group within the bacterial tree of life, some people suggested that they do not reproducibly affiliate with other Proteobacteria. 39 The expression of non-Helicobacter Proteobacteria appeared to distinguish Helicobacter from Proteobacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 A number of authors grouped Helicobacter into Proteobacteria in their articles. 14,16 While the Epsilonproteobacteria constitute a stable monophyletic group within the bacterial tree of life, some people suggested that they do not reproducibly affiliate with other Proteobacteria. 39 The expression of non-Helicobacter Proteobacteria appeared to distinguish Helicobacter from Proteobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The Epsilonproteobacteria used to be the fifth validly described class of the phylum Proteobacteria, it was widely known for its pathogenic genera Helicobacter 39 . A number of authors grouped Helicobacter into Proteobacteria in their articles 14,16 . While the Epsilonproteobacteria constitute a stable monophyletic group within the bacterial tree of life, some people suggested that they do not reproducibly affiliate with other Proteobacteria 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, in H. pylori -positive subjects, there is an increased abundance of Proteobacteria, likely due to the contribution of H. pylori itself, while the abundance of Actinobacteria, Bacteroidetes, Fusobacteria, and Firmicutes is reduced [ 79 , 81 ]. In a study by Wang et al, some species, such as Stenotrophomonas maltophilia , Chryseobacterium unclassified , Pedobacter unclassified , Stenotrophomonas unclassified , Variovorax unclassified , and Pseudomonas stutzeri , have been associated with the presence of H. pylori infection, through the shotgun sequencing of stomach swab samples of 96 patients [ 82 ]. On the other hand, in a rhesus macaque model, Martin et al observed the impact of H. pylori on the antecedent gastric microbiota and found no significant variations in the relative abundance of non-Helicobacter taxa, indicating that in the rhesus macaque model, the gastric microbiome is stable despite the presence of the H. pylori infection [ 83 ].…”
Section: The Effect Of H Pylori On Gastric Microbiotamentioning
confidence: 99%
“…Other studies have reported the decrease in microbial richness and diversity in GC patients, especially in those with HP ( Ferreira et al, 2018 ; Liu et al, 2019 ). Wang et al (2022) performed metagenomic shotgun sequencing on stomach swab samples from 96 patients with GC, and then conducted metagenomic association analysis between changes in stomach microbiota and HP infection status. It was found that HP became the dominant species after colonization in human stomach, and significantly reduced the α diversity of gastric community.…”
Section: Relationship Between Microorganisms and Gastric Cancermentioning
confidence: 99%